Information systems and sustainable supply chain management towards a more sustainable society: Where we are and where we are going - Fiorini, Paula de Camargo [UNESP]; Jabbour, Charbel Jose Chiappetta (Elsevier B.V., 2017)
The objectives of this study are to identify and systematize scholarly articles on the use of information system to support sustainable supply chain management and to suggest future research opportunities. Therefore, a structured literature review was conducted. The most relevant studies identified were classified and categorized into seven dimensions: research context, research focus, research method, sector analyzed, information system (IS) beneficiaries, relationship between IS and green supply chain practices, and performance benefits. The main authors and articles on this particular topic were identified. In addition, it was concluded that IS is an important support tool for sustainable supply chain management practices since it brings benefits to the organization, suppliers, and customers. Furthermore, IS positively influences the operational, financial, and environmental performance of the organization. However, further advances in the literature are still needed. The major contribution of this research is related to the recommendations that provide opportunities for future research. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Information systems for sustainable development; Sustainable supply chain management; Green supply chain management; Sustainable development; Green information systems; Sustainable IT